Morphophysiological responses of tomato phytochrome mutants under sun and shade conditions - Mereb, Emiliana Licio; Alves, Frederico Rocha Rodrigues; Rezende, Maria Helena; De Oliveira, Eliaby Jose; Carvalho, Rogerio Falleiros [UNESP]; De Melo, Hyrandir Cabral (Soc Botanica Sao Paulo, 2020)
Phytochromes (PHYs) have long been associated with classic photomorphogenic responses and recently implied with the regulation of plant productivity. We aimed to characterize these links in an important agronomic crop such as tomato (cv. Moneymaker) by evaluating biomass partitioning and morphophysiological parameters related to productivity under distinct light conditions in phyA, phyB1 and phyB2 tomato mutants. Under sun, PHY mutants presented lower leaf biomass during the vegetative phase the same way as the wild type (WT) under shading treatment. However, no difference regarding fruit biomass ratio (harvest index) was registered between WT and PHY mutants. phyA was the shortest genotype with lesser lateral branches and smaller xylem vessels and alongside phyB1, presented lesser leaf area. Net photosynthesis rate and photosystem II maximum potential quantum efficiency were not affected by phytochrome loss under sun condition. Nevertheless, PHY mutants showed lesser chlorophyll a content and stomata conductance and transpiration rates. Together, our data reveal that despite some morphophysiological and developmental impairments and the differences in biomass accumulation associated with the distinct PHYs under distinct light conditions, the plant harvest index is not affected by individual PHY losses under sun condition.
Keywords: Photomorphogenesis; Photosynthate partitioning; Photosynthesis; Solanum lycopersicum